Hubungan Dukungan Keluarga dengan Tingkat Kecemasan pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di Rumah Sakit Primaya Bekasi Barat - Cusmarih, Cusmarih; Perdana, Bima Putra (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Chronic renal failure (CKD) is a progressive decline in kidney tissue function so that the remaining kidney mass is no longer able to maintain the body's internal environment (Ariga, 2020). According to WHO (World Health Organization) data, the prevalence of kidney failure in the world according to ESRD Patients (End-Stage Renal Disease) in 2017 was 2,786,000 people, in 2019 it was 3,018,860 people and in 2020 it was 3,200,000 people. From these data, it can be concluded that there is an increase in the morbidity rate of kidney failure patients every year by 6%. Around 78.8% of chronic kidney failure patients in the world use dialysis therapy for survival (Ariga, 2020). To determine the relationship between family support and anxiety levels in chronic kidney failure patients undergoing hemodialysis at Primaya Hospital, West Bekasi in 2024. This research method is quantitative using a cross sectional approach. The analysis used is univariate analysis and bivariate analysis. The population in this study was all patients with chronic kidney failure from December 2024 to January 2025. The research location was carried out at Primaya Hospital, West Bekasi, for 4 weeks from December 2024 to January 2025. Based on the results of Bivariate Analysis with the Chi-Square test, it was found that respondents who had high family support (score > 40) had 25 (69.4%) non-anxious levels of anxiety, 6 (6.7%) respondents who experienced mild anxiety and there was no data on respondents with moderate anxiety and severe anxiety. Likewise, respondents who had moderate family support (score 21-39) experienced mild levels of anxiety, namely 3 (8.3%) respondents and 2 (5.5%) respondents experienced moderate anxiety and there was no data on respondents who were not anxious and had severe anxiety. Then no data was found on respondents with low levels of family support (score <20).  There is an influence between family support and the level of anxiety in chronic kidney failure patients undergoing hemodialysis at Primaya Hospital, West Bekasi in 2024. In the Chi-square test, the P value was obtained which showed a value of 0.000, which means P value <0.05. Keywords: Hypertension, Elderly, and Foot Massage ABSTRAK Gagal ginjal kronik(GGK) merupakan suatu penurunan fungsi jaringan ginjal secara progresif sehingga masa ginjal yang masih ada tidak mampu lagi mempertahankan lingkungan internal tubuh (Ariga, 2020). Menurut Data WHO (World Health Organization) mengemukakan bahwa prevalensi gagal ginjal di dunia menurut ESRD Patients (End-Stage Renal Disease) pada tahun 2017 sebanyak 2.786.000 orang, tahun 2019 sebanyak 3.018.860 orang dan tahun 2020 sebanyak 3.200.000 orang. Dari data tersebut disimpulkan adanya peningkatan angka kesakitan pasien gagal ginjal tiap tahunnya sebesar sebesar 6 %. Sekitar 78,8% dari pasien gagal ginjal kronik di dunia menggunakan terapi dialisis untuk kelangsungan hidupnya (Ariga, 2020). Untuk mengetahui hubungan dukungan keluarga dengan tingkat kecemasan pada pasien gagal ginjal kronik yang menjalani hemodialisa di rumah sakit primaya bekasi barat tahun 2024. Metode penelitian ini adalah kuantitatif dengan menggunakan pendekatan cross sectional. Analisis yang digunakan yaitu analisisi univariat dan analisis bivariat. Populasi dalam penelitian ini adalah seluruh pasien gagal ginjal kronik pada bulan Desember 2024 hingga Januari 2025. Tempat penelitian dilakukan di Rumah Sakit Primaya Bekasi Barat dilakukan selama 4 minggu pada bulan Desember 2024 hingga Januari 2025. Berdasarkan hasil Analisis Bivariat dengan uji Chi-Square diketahui bahwa responden yang memiliki dukungan keluarga tinggi (skor >40) mempunyai tingkat kecemasan tidak cemas sebanyak 25 (69,4%), responden yang mengalami kecemasan ringan sebanyak 6 (6,7%) responden dan tidak terdapat data responden dengan cemas sedang dan cemas berat. Begitu juga dengan responden yang meililiki dukungan keluaga sedang (skor 21-39) mengalami tingkat kecemasan yang ringan yaitu 3 (8,3%) responden dan 2 (5,5%) responden  mengalami kecemasan sedang dan tidak terdapat data responden tidak cemas dan cemas berat. Kemudian tidak ditemukan data responden dengan tingkat dukungan keluarga rendah (skor <20). Ada pengaruh hubungan dukungan keluarga dengan tingkat kecemasan pada pasien gagal ginjal kronik yang menjalani hemodialisa di Rumah Sakit Primaya Bekasi Barat tahun 2024. Pada uji Chi-square, di dapatkan hasil  P Value yang menunjukkan nilai 0.000 yang berarti P Value <0.05. Kata Kunci: Gagal Ginjal Kronik, Dukungan Keluarga, Tingkat Kecemasan, Hemodialisa